Туристический имидж Крыма: от формирования образа к управлению репутацией - Володченко, О.Н. (Культура народов Причерноморья, 2014)
В статье рассматривается феномен имиджа как невещественного капитала, который
приносит дополнительные, финансовые дивиденды, так называемый, репутационный капитал Помимо
этого акцентируется внимание на технологиях, которые используются при формировании
туристического имиджа территории. Даются практические рекомендации по повышению
эффективности технологий при формировании имиджа и управлении репутационным капиталом. У статті розглядається феномен іміджу як нематеріального активу, який приносить
додаткові, фінансові дивіденди, так званий, репутаційний капітал. Окрім цього акцентується увага на
технологіях, які використовуються при формуванні туристичного іміджу території. Даються
практичні рекомендації щодо підвищення ефективності технологій при формуванні іміджу і управлінні
репутаційним капіталом. In the article the phenomenon of image is examined as immaterial capital, which brings extra
financial dividends, so-called, reputation capital. In the modern world an intangible concept – reputation – grew
into financial goodwill and became one of the major intangible assets of firm, estimated in its annual bookkeeping
balance.
PR-technologies are the most effective in the forming of the territory image as they work on a having a special
purpose audience and are effective in adjustingthe dialog. Therefore the attention is accented on
technologieswhich are used for forming of the territory tourist image, and also practical recommendations on
the increaseof efficiency of image forming technologies and the reputation capital management are given in the
article. The author comes to the conclusion that creation of the program of forming of Crimea tourist image is
necessary and points out the necessity of the usage of different types of communication: publicity, marketing,
mass and communications in the field of public relations for the tourist product advancement to the international
market.